Pain Management in Enhanced Recovery after Surgery (ERAS) Protocols - Simpson, J. Creswell; Bao, Xiaodong; Agarwala, Aalok (Clinics in Colon and Rectal Surgery, 2019)
Pain control is an integral part of Enhanced Recovery after Surgery (ERAS) protocols for colorectal surgery. While opioid therapy remains the mainstay of therapy for postsurgical pain, opioids have undesired side effects including delayed recovery of bowel function, respiratory depression, and postoperative nausea and vomiting. A variety of nonopioid systemic medical therapies as well as regional and neuraxial techniques have been described as improving pain control while reducing opioid use. Multimodal and preemptive analgesia as part of an ERAS protocol facilitates early mobility and early return of bowel function and decreases postoperative morbidity. In this review, we examine several multimodal therapies and their impact on postoperative analgesia, opioid use, and recovery for patients undergoing colorectal surgery.
Keywords: ERAS; multimodal analgesia; pain management; colorectal surgery